Platelet cytochrome oxidase and citrate synthase activities in APOE ε4 carrier and non-carrier Alzheimer's disease patients - Wilkins, Heather M.; Koppel, Scott J.; Bothwell, Rebecca; Mahnken, Jonathan; Burns, Jeffrey M.; Swerdlow, Russell H. (Redox biology, 2017)
A degradation product of APOE ε4-encoded apolipoprotein E protein targets mitochondria and inhibits cytochrome oxidase (COX), and autopsy brains from young adult APOE ε4 carriers show reduced COX activity. To further explore relationships between APOE alleles and COX, we measured platelet mitochondria COX activity in AD subjects with (n=8) and without (n=7) an APOE ε4 allele and found the mean COX activity, when normalized to sample total protein, was lower in the APOE ε4 carriers (p<0.05). Normalizing COX activity to citrate synthase (CS) activity eliminated this difference, but notably the mean CS activity was itself lower in the APOE ε4 carriers (p<0.05). COX and CS protein levels did not appear to cause the lower APOE ε4 carrier COX and CS Vmax activities. If confirmed in larger studies, these data could suggest mitochondria at least partly mediate the well-recognized association between APOE alleles and AD risk.